2023
DOI: 10.1177/1759720x231189008
|View full text |Cite
|
Sign up to set email alerts
|

New insights in lower limb reconstruction strategies

Abstract: High Energy Musculoskeletal Traumas (HEMTs) represent a relevant problem for healthcare systems, considering the high social costs, and both the high morbidity and mortality. The poor outcomes associated with HEMT are related to the high incidence of complications, including bone infection, fracture malunion and non-union. The treatment of each of these complications could be extremely difficult. Limb reconstruction often needs multiple procedures, rising some questions on the opportunity in perseverate to try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Traumatic major limb mutilation is one of the main causes of limb loss. Even though replantation of limb mutilation is increasing gradually with the development of microsurgery and surgical techniques [ 1 , 4 , 27 ], postoperative wound infection can result in multiple operations and even delayed amputation, which may increase the financial and psychological burden of patients [ 2 , 4 , 16 ]. This study found that postoperative wound infection was common in patients with severe traumatic major limb mutilation, and most of the pathogenic bacteria were multi-drug resistant bacteria, which was associated with ischemic time, degrees of wound contamination, stress hyperglycemia, and MESS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic major limb mutilation is one of the main causes of limb loss. Even though replantation of limb mutilation is increasing gradually with the development of microsurgery and surgical techniques [ 1 , 4 , 27 ], postoperative wound infection can result in multiple operations and even delayed amputation, which may increase the financial and psychological burden of patients [ 2 , 4 , 16 ]. This study found that postoperative wound infection was common in patients with severe traumatic major limb mutilation, and most of the pathogenic bacteria were multi-drug resistant bacteria, which was associated with ischemic time, degrees of wound contamination, stress hyperglycemia, and MESS.…”
Section: Discussionmentioning
confidence: 99%
“…High energy trauma such as traumatic mutilation of major limbs was the leading cause of amputation and can be life-threatening [1][2][3]. With the development of surgical techniques, the limbs saving rate of patients gradually increased [1,4], however, with the aggravation of trauma severity, the incidence of postoperative complications also gradually increased [2,5,6]. Postoperative wound infection is one of the most common complications after surgery [7,8].…”
Section: Introductionmentioning
confidence: 99%